2020
DOI: 10.3390/ijms21165676
|View full text |Cite
|
Sign up to set email alerts
|

Role of Excitatory Amino Acid Carrier 1 (EAAC1) in Neuronal Death and Neurogenesis After Ischemic Stroke

Abstract: Although there have been substantial advances in knowledge regarding the mechanisms of neuron death after stroke, effective therapeutic measures for stroke are still insufficient. Excitatory amino acid carrier 1 (EAAC1) is a type of neuronal glutamate transporter and considered to have an additional action involving the neuronal uptake of cysteine, which acts as a crucial substrate for glutathione synthesis. Previously, our lab demonstrated that genetic deletion of EAAC1 leads to decreased neuronal glutathione… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Neurons in the rat cerebral cortex, hippocampus, cerebellum, and spinal cord express the EAAC1 transporters (Kanai et al, 1995 ; Shashidharan et al, 1997 ). Interestingly, this transporter is mainly involved in anion conductance and uptake of cysteine, a precursor of glutathione synthesis (Lee et al, 2020 ). EAAT4 is highly expressed in cerebellar Purkinje cells (Magi et al, 2019 ).…”
Section: Glutamatergic Neurotransmissionmentioning
confidence: 99%
“…Neurons in the rat cerebral cortex, hippocampus, cerebellum, and spinal cord express the EAAC1 transporters (Kanai et al, 1995 ; Shashidharan et al, 1997 ). Interestingly, this transporter is mainly involved in anion conductance and uptake of cysteine, a precursor of glutathione synthesis (Lee et al, 2020 ). EAAT4 is highly expressed in cerebellar Purkinje cells (Magi et al, 2019 ).…”
Section: Glutamatergic Neurotransmissionmentioning
confidence: 99%
“…These malignant characteristics were weakened to a great degree after long-term treatment with AMPA receptor antagonists and calpain inhibitors, reflecting that excessive activation of AMPA and intracellular calcium overload after glutamate transporter deficiency are the pathological mechanisms that mediate motoneuron death [ 178 ]. In addition, Minwoo Lee [ 179 ] et al proved that EAAT3 knockout could also aggravate neuronal death after tMCAO and inhibit the proliferation and repair of hippocampal cells themselves.…”
Section: Glutamate Uptake and Metabolic Inhibition Aggravating Synapt...mentioning
confidence: 99%
“…In particular, neuron EAAT3 is thought to be involved in the extra uptake of cysteine and is responsible for the conversion of glutamate into reactive oxygen species (ROS) scavenger glutathione [ 181 ]. It has been confirmed that the aggravation of ischemic injury caused by EAAT3 deletion is mainly attributed to the decrease in glutathione synthesis and the increase in oxidative stress [ 179 ]. Other studies have also shown that drugs promoting the glutamate–glutathione metabolic cycle can reduce glutamate and synaptic excitability, thus having a detoxification effect [ 182 ].…”
Section: Glutamate Uptake and Metabolic Inhibition Aggravating Synapt...mentioning
confidence: 99%
“…All NSCs exist in the heterogeneous state, which undergoes both symmetric division (functional self-renewal) or asymmetric division (one mature to neuron). In both niches, NSCs migrate to certain brain regions and differentiate to immature neurons, showing hyperexcitability and increased susceptibility to synaptic inputs [ 74 ]. The process of neurogenesis in SGZ begins with glial fibrillary acidic protein (GFAP)-positive radial glial-like NSCs (type I cells) in SGZ turning into GFAP-negative progenitors (type II cells) in the granular cell layer [ 75 , 76 , 77 ].…”
Section: Noxs and Neurogenesismentioning
confidence: 99%